Rosalind and "Śakuntalā" among the Ascetics: Reading Gender and Female Sexual Agency in a Bengali Adaptation of "As You Like It" - Sarkar, Abhishek (Multicultural Shakespeare: Translation, Appropriation and Performance, 2018)
My article examines how the staging of gender and sexuality in Shakespeare’s play As You Like It is negotiated in a Bengali adaptation, Ananga-Rangini (1897) by the little-known playwright Annadaprasad Basu. The Bengali adaptation does not assume the boy actor’s embodied performance as essential to its construction of the Rosalindequivalent, and thereby it misses several of the accents on gender and sexuality that characterize Shakespeare’s play. The Bengali adaptation, while accommodating much of Rosalind’s flamboyance, is more insistent upon the heteronormative closure and reconfigures the Rosalind-character as an acquiescent lover/wife. Further, Ananga-Rangini incorporates resonances of the classical Sanskrit play Abhijñānaśākuntalam by Kālidāsa, thus suggesting a thematic interaction between the two texts and giving a concrete shape to the comparison between Shakespeare and Kālidāsa that formed a favourite topic of literary debate in colonial Bengal. The article takes into account how the Bengali adaptation of As You Like It may be influenced by the gender politics informing Abhijñānaśākuntalam and by the reception of this Sanskrit play in colonial Bengal.